2007
DOI: 10.1007/s12031-007-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Specific Increase of Phosphatidylserine by Docosahexaenoic Acid

Abstract: Phosphatidylserine (PS), the major acidic phospholipid class in eukaryotic biomembranes, plays an important role in various signaling pathways. We have previously demonstrated that docosahexaenoic acid (DHA, 22:6n-3) positively modulates PS biosynthesis and accumulation in neuronal cells, promoting survival. In this paper, we demonstrate that the increase of PS levels upon DHA enrichment is not a universal mechanism, but specific to neuronal cells. When cells were enriched with 20 muM DHA, 18:0, 22:6-PS increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 34 publications
(28 reference statements)
1
22
0
Order By: Relevance
“…Only the cells enriched with DHA in a serine depleted condition showed inhibited PS accumulation in agreement with the serine requirement for the mammalian PS synthesis using the serine-base exchange reaction. Similarly, over-expressing pss1 and pss2 genes cloned from the liver (Stone and Vance, 1999;Sturbois-Balcerzak et al, 2001) in non-neuronal cells did not increase the PS accumulation (Guo et al, 2007). These data suggest that PS levels are tightly regulated in living cells and these highly unsaturated very long chain fatty acids are uniquely capable of expanding the PS pool specifically in neuronal cells.…”
Section: Regulation Of Phosphatidylserine Accumulation In Cultured Cellsmentioning
confidence: 77%
See 1 more Smart Citation
“…Only the cells enriched with DHA in a serine depleted condition showed inhibited PS accumulation in agreement with the serine requirement for the mammalian PS synthesis using the serine-base exchange reaction. Similarly, over-expressing pss1 and pss2 genes cloned from the liver (Stone and Vance, 1999;Sturbois-Balcerzak et al, 2001) in non-neuronal cells did not increase the PS accumulation (Guo et al, 2007). These data suggest that PS levels are tightly regulated in living cells and these highly unsaturated very long chain fatty acids are uniquely capable of expanding the PS pool specifically in neuronal cells.…”
Section: Regulation Of Phosphatidylserine Accumulation In Cultured Cellsmentioning
confidence: 77%
“…Consistent with the brain microsomal PS biosynthetic activity shown above, DHA was more effective in accumulating PS in comparison to DPAn6. Non-neuronal cell lines including CHO-K1, NIH-3T3, HEK-293 and HELA did not increase total PS in response to DHA or DPAn6, suggesting that the phospholipid profile is differently regulated in neuronal cells (Guo et al, 2007). The molecular species analysis by electrospray HPLC/MS indicated that DHA was incorporated into PS mainly as 18:0,22:6 species also in non-neuronal cells.…”
Section: Regulation Of Phosphatidylserine Accumulation In Cultured Cellsmentioning
confidence: 91%
“…Consistently, hippocampal neurons from DHA-depleted animals showed reduced amounts of PS and were more susceptible to cell death. As opposed to the findings with Neuro 2A cells, DHA supplementation did not increase the PS content in Chinese hamster ovary-K1 cells, NIH3T3 cells or HEK cells, suggesting that the PS increase induced by DHA occurs primarily in neuronal cells [180]. The protective action of DHA did not occur when Neuro 2A cells were incubated in a serine-free medium, suggesting that this effect is PS-dependent [2,4].…”
Section: Interactions Between Phosphatidylserine and Docosahexaenomentioning
confidence: 82%
“…DHA increases phosphatidylserine (PS) in neuronal cells and in turn translocates AKT from the cytosol to the membrane after ischemia; a required step for phosphorylation and activation of AKT [17], [18]. Here we have explored downstream AKT phosphorylation events.…”
Section: Introductionmentioning
confidence: 99%